THE HOLISTIC APPROACH IN EDUCATION DEVELOPMENT PROGRAMS: CASE OF INDONESIA MENGAJAR - Fibra, Adsina; Berewot, Juliana (Bina Nusantara University, 2019)
This paper aims to describe one of sustainable projects of improving education quality in archipelagic nations. Indonesia Mengajar is an Indonesian NGO based in Jakarta which promotes volunteerism by being young educators. Their projects aim to fill the shortage of primary school teachers, especially in remote areas. By sending the best Indonesian university graduates which have been intensively trained to work as teachers for one consecutive year, it was expected they will be able to inspire young people to choose careers as educators. It is a qualitative study on how the organization plans and executes their projects. The findings stimulate further questions on how to solve the issue of quality education in Indonesia.